Total ozone and Umkehr observations at Hoher Sonnblick 1994–2011: Climatology and extreme events. Issue 2 (31st January 2014) - Fitzka, M.; Hadzimustafic, J.; Simic, S.
<x xml:space="preserve">Abstract</x> Umkehr and total ozone measurements have been carried out at Hoher Sonnblick (47.05°N, 12.95°E; 3106 m above sea level) since 1994 with the Brewer MkIV #093 spectrophotometer. These measurements are used to investigate trends in total and vertically resolved ozone in the period 1994–2011 and for establishing an Umkehr climatology. A method to estimate daily thresholds for extreme events in total ozone (TO3) based on skewed log‐Weibull distributions is presented and applied to the record. An analysis of the such defined extreme events reveals a significant decline in the number of low events, whereas the high events increased by about the same amount. However, no significant trend is observed in the magnitude of extreme events. Solar activity and equivalent effective stratospheric chlorine show weak to no correlation with vertically resolved ozone, presumably due to the record's limited extent, while tropopause pressure and quasi‐biennial oscillation show a significant influence. Trend analysis of total and vertically resolved ozone indicates a significant increase in TO3 of 2.0% per decade since 1994, whereas no recovery is observed in the upper stratosphere. While ozone concentrations continue to decrease or stagnate in the upper stratosphere, the loss is overcompensated by large gains in the lowest layers during winter, leading to a significant overall increase in TO3. During events with extremely low TO3, the largest deficiencies are found in the bottommost layers with a marked seasonal component. The topmost layers mainly contribute to TO3 reductions during late winter and fall.